Optimization of subsea arrangement for production system - Hong, Cheng (2019)
This thesis presents the optimization of subsea production system arrangement, focusing on two basic concepts: satellite well system with Floating Production Storage Offloading unit (FPSO), and manifold system with FPSO, respectively. Two typical scenarios for each concept are considered to establish the optimization models: satellite well system considering vertical wells, satellite well system considering horizontal wells, manifold system with satellite distributed vertical wells and manifold system with clustered horizontal wells. The models are developed through mixed-integer programming (MIP). Three major objectives are considered: lowest cost, shortest payback period, and minimum pressure loss. Through the proposed optimization models, the subsea flowline network, flowline route, FPSO processing capacities, manifold sizes and locations (for the manifold system), wellhead locations and well trajectories, and well production rates could be figured out. The proposed MIP models are with nonlinearities. Based on the gradient descent algorithm, the MIP models are decomposed to a series of linear models, which are solved by optimizer GUROBI. The final optimal solutions are obtained through the iteration process. The Delaunay triangulation method is applied to discrete the solution space in order to obtain good initial solutions. The proposed models are applied to the arrangement optimization of the same offshore field, and the results of different scenarios are compared, as well as the results of different objective functions. The case studies indicate good performance of the proposed models and solution method, providing convenient and reliable tools for real-world applications.